2020
DOI: 10.1192/j.eurpsy.2020.59
|View full text |Cite
|
Sign up to set email alerts
|

The social psychological impact of the COVID-19 pandemic on medical staff in China: A cross-sectional study

Abstract: Abstract Background. The COVID-19 outbreak required the significantly increased working time and intensity for health professionals in China, which may cause stress signs. Methods. From March 2–13 of 2020, 4,618 health professionals in China were included in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
124
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 28 publications
10
124
0
18
Order By: Relevance
“…It has been noted that the health-care workers are encountering far more emotional stress compare with the general population, during the COVID-19 pandemic [37,38]. Increased workload, working with repeatedly changing protocols, using PPE, social-distancing, self-isolation, and caring for deteriorating patients are found to be the main concerns among the medical staff during the pandemics [39,40]. Moreover, difficult decisions should be made by the workers during the pandemics as the resources are limited [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the health-care workers are encountering far more emotional stress compare with the general population, during the COVID-19 pandemic [37,38]. Increased workload, working with repeatedly changing protocols, using PPE, social-distancing, self-isolation, and caring for deteriorating patients are found to be the main concerns among the medical staff during the pandemics [39,40]. Moreover, difficult decisions should be made by the workers during the pandemics as the resources are limited [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the health-care workers are encountering far more emotional stress compare with the general population, during the COVID-19 pandemic (38,39). Increased workload, working with repeatedly changing protocols, using PPE, social-distancing, self-isolation, and caring for deteriorating patients are found to be the main concerns among the medical staff during the pandemics (40,41). Moreover, di cult decisions should be made by the workers during the pandemics as the resources are limited (42).…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature have reported that the prevalence of psychological symptoms in medical health workers during the COVID-19 epidemic is higher than in the past epidemics [15]. Increased concerns in the medical staff and their families can have a negative impact on the provision of health services, which can subsequently discourage and isolate the patients [16].…”
Section: Introductionmentioning
confidence: 98%